2005
DOI: 10.1007/s10661-005-1620-x
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Mercury Removal from Topsoil Using Low-Thermal Application

Abstract: Mercury contamination in the environment is problematic due to the unusual physical properties and well-recognized toxicity of this common metal. The bioavailability of mercury depends strongly on its chemical speciation. Anthropogenic mercury and its compounds appear in soil as "hot spots" located close to industrial facilities that used or produced mercury. The nature of the chemical production process, transportation and disposal practices often determined the chemical composition and distribution of mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In these thermal devices, the off-gas generated is passed through a filtration system, where Hg 0 , finally, is collected [3,4]. Several mercury desorption experiments have demonstrated the feasibility of mercury removal at temperatures between 127 and 600 °C [5][6][7][8]. Experimental remediation of mercury-polluted soils by low-temperature thermal desorption has also shown mercury removal of over 99% in sand [8] and the volatilization of at least 99% of mercuric sulfide from polluted soil [5].…”
Section: Open Accessmentioning
confidence: 99%
“…In these thermal devices, the off-gas generated is passed through a filtration system, where Hg 0 , finally, is collected [3,4]. Several mercury desorption experiments have demonstrated the feasibility of mercury removal at temperatures between 127 and 600 °C [5][6][7][8]. Experimental remediation of mercury-polluted soils by low-temperature thermal desorption has also shown mercury removal of over 99% in sand [8] and the volatilization of at least 99% of mercuric sulfide from polluted soil [5].…”
Section: Open Accessmentioning
confidence: 99%
“…These data provide easily available Hg for plants which is the essential Hg from the agricultural point of view. Kucharski et al (2005) investigated the remediation of Hgcontaminated soil using thermal desorption with operating conditions of 100°C for 10 days and found that the most mobile and toxic Hg species were removed. In the present work, it is observed that another factor to consider besides time is the temperature increase since the concentration of these species changes with it.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Bloom's method (Miller et al 2013), there are other procedures used to determine the fractions of Hg in soil and how these fractions changed as a result of a remediative process. For example, many studies separate soil-bound Hg into six fractions: water soluble (extraction with deionized water), exchangeable (extraction with 1 M CH 3 COONH 4 ), elemental mercury (by heating in an oven for 48 h at 373 K), fulvic and humic acids (extraction with 1 M KOH and acidification to pH 2), organic and sulfide (extraction with 0.1 M HNO 3 and H 2 O 2 ), and the residual (extraction with aqua regia) (Biester and Scholz 1997;Di Giulio and Ryan 1987;Kucharski et al 2005). A sequential extraction procedure proposed by the Community Bureau of Reference (BCR) (Ure et al 1993) was also adopted by researchers for Hg fractionation Subires-Munoz et al 2011).…”
Section: Chemistry Of Mercury and Implications For Soil-sediment Remementioning
confidence: 99%
“…3). Kucharski et al (2005) tested thermal desorption at laboratory and pilot scale using mercury-contaminated soils from a chlor-alkali production site in southern Poland, with an ultimate goal to apply this process in situ. In the laboratory experiment, soil temperature was raised from 40 to 60°C, while in the pilot-scale experiment, soil was heated to a maximum average temperature of 167°C.…”
Section: In Situ Mercury Removal Technologiesmentioning
confidence: 99%
See 1 more Smart Citation